UUpaya Instruktur dalam Memberdayakan Warga Binaan melalui Pelatihan Las Smaw - Amalia, Iin; Djumena, Irwan; Suherman, Suherman (Journal of Nonformal Education and Community Empowerment, 2018)
This research is conduted to find out (1) what is the effort of the instructor in empowering the studens to learn the SMAW welding training at the Training Center (BLK) of Pandeglang Regency? (2) How is the result of the SMAW welding training program in empowering the learners by the instructor at the Training Center (BLK) Pandeglang District? (3) What are the supporting factors and inhibiting factors experienced by the instructor in empowering the learners in the SMAW welding training at the Pandeglang District Training Center (BLK)?. Research method used by writer in this research is descriptive with qualitative approach. In this research with qualitative approach should be based on data or information obtained through research as follows: (1) Interview, (2) Observation, (3) Documentation. The stage of data collection in this research is the orientation stage, exploration stage and member check stage. Processing techniques and data analysis include the reduction phase, data presentation and verification phase. The data source of this research is the instructor and the residents learn at the Training Center (BLK) Pandeglang District. As the end of this discussion, the authors convey the folloswing conclusions: 1. The efforts of the instructor in empowering the people to learn through SMAW welding training at Pandeglang District Training Center (BLK) are a) Creating a climate that enables the potential of developing society (Enabling) b) Actualizing the potential already possessed by the community (Empowering), c) Empowering means also protect (Protecting), 2. The results of the instructor's efforts in empowering the learners through welding training in BLK Pandeglang District are: a) Cognitive, b) Affective, c ) Psychomotor, 3. Supporting factors and inhibiting factors experienced by the instructor in empowering the learners through the SMAW welding training are skilled instructors, the high spirit of the learning community, and the strategic location. While the inhibiting factors are facilities and infrastructure.